We have
"2(y+z)dx-(x+z)dy+(2y-x+z)dz=0" General form of the Pfafffian equation is
"Pdx+Qdy+Rdz=0" The integrability condition for the Pfaffian equation is
"(curlF, F)=0" where "F=(P, Q, R)," or
"P({\\eth Q \\over \\eth z}-{\\eth R \\over \\eth y})+Q({\\eth R \\over \\eth x}-{\\eth P \\over \\eth z})+R({\\eth P \\over \\eth y}-{\\eth Q \\over \\eth x})=0"Verify
"P=2(y+z), Q=-(x+z), R=(2y-x+z)""2(y+z)(-1-2)-(x+z)(-1-2)+(2y-x+z)(2+1)=""=-6y-6z+3x+3z+6y-3x+3z=0"The integrability condition for this equation hold.
If the Pfaffian equation is multiplied by a certain function "\\mu(x, y,z)" then one can obtain in the
left-hand side the total differential.
If we treat "z" as a constant, then the given equation reduces to
"2(y+z)dx-(x+z)dy=0""{2 \\over x+z}dx-{1 \\over y+z}dy=0" which has a solution
"U(x, y, z)={(x+z)^2 \\over y+z}=C_1"The integrating factor "\\mu(x,y,z)" is given by
"\\mu={1 \\over P}\\cdot {\\eth U \\over \\eth x}={1 \\over 2(y+z)}\\cdot {2(x+z) \\over y+z}={x+z \\over (y+z)^2}" We have
"K=\\mu R-{\\eth U \\over \\eth z}=""={x+z \\over (y+z)^2}(2y-x+z)-{2(x+z)(y+z)-(x+z)^2 \\over (y+z)^2}=""={x+z \\over (y+z)^2}(2y-x+z-2y-2z+x+z)=0" Thus we have the equation
"dU=0" which has a solution "U=c"
Thus the solution of the given equation
"(x+z)^2=c(y+z)"
where "c" is a constant.
Comments
Leave a comment